DIPLOMASI PUBLIK INDONESIA TERHADAP MESIR DALAM MENINGKATKAN EKSPOR KOPI PERIODE 2020-2021 - Aji Adira Fadia Putri Padmo, (2023)
This study aims to analyze the role of Indonesia's public diplomacy towards Egypt in increasing coffee exports for the 2020-2021 period. Public diplomacy is a strategy used by the Indonesian government to boost Indonesia's economy during the crisis due to the pandemic COVID-19 by promoting and increasing coffee exports to partner countries such as Egypt. The research method used is a qualitative approach. The data used consists of primary and secondary sources, including official documents, statistical reports, and interviews with stakeholders such as government officials and coffee exporters. The results showed that Indonesia's public diplomacy towards Egypt positively impacted increasing coffee exports. Through intensive diplomatic efforts, such as bilateral meetings, trade fairs, and increased promotion of Indonesian coffee in Egypt, Indonesian coffee exports to Egypt increased significantly in 2020-2021.